Hubungan Pengetahuan Terhadap Perawatan Luka Modern Dressing dengan Tingkat Kesembuhan Luka Diabetikum - Rosadi, Erik; Putri, Anggy Utama (JURNAL KESEHATAN TERAPAN, 2024)
Diabetic ulcer and gangrene cases are the most well-known cases treated in clinics. The death rate due to ulcers and gangrene goes from 17-23%, while the removal rate goes from 15-30%, the permanent demise rate 1 year after removal is 14.8%. The third year saw an increase in this number to 37%. After amputation, the average age of the patients was only 23.8 months. An analytical survey with a cross-sectional design was used in this study to collect the independent and dependent variables simultaneously. Chi-square was used for statistical tests. This study used a sample of 36 people. In this review, in light of the Chi-Square factual test, the P-esteem = 0.016 <0.05 was gotten, the job of the family isn't great in current dressing wound care has the open door to no avail. While the job of the family got a p esteem = 0.029 <0.05, unfortunate information for not recovering. it tends to be reasoned that there is a critical connection among information and the job of the family in present day wound dressing care with the degree of mending of diabetic injuries at the Inner Medication Polyclinic of the Siti Khadijah Islamic Emergency clinic, Palembang.